Nuclear mean-field models and super-heavy elements - Reinhard, Paul-Gerhard (Walter Greiner Memorial Volume, 2018)
This article reviews the description of super-heavy elements (SHE) in terms of self-consistent mean-field models. The Skyrme-Hartree-Fock (SHF) approach is taken as one typical example for such models in the family of nuclear density functional theories. The tour starts with the search for new magic numbers, continues with estimates of stabilization of SHE through the shell-correction energy, and rounds up with a discussion fission barriers and lifetimes as the finally decisive quantities for the existence of SHE.
CRIS-Team Scopus Importer:2023-07-24